2009
DOI: 10.1097/pgp.0b013e318182c2be
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor (VEGF), Hypoxia Inducible Factor-1α (HIF-1α), and Microvessel Density in Endometrial Tissue in Women With Adenomyosis

Abstract: Adenomyosis is a disease with a mysterious pathogenesis, defined by an abnormal displacement of the eutopic endometrium deeply and haphazardly inside the myometrium. Angiogenesis has been indicated to play an important role and our aim was to investigate whether vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1alpha (HIF-1alpha) expression and microvessel density (MVD) were different in women with and without adenomyosis. Immunohistochemistry was performed in endometrial tissues in 23 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 29 publications
2
62
2
3
Order By: Relevance
“…Similar results for MMP2 were obtained by Tokyol et al (2009). Subsequently, Goteri et al (2009) compared in the same women the expression of VEGF and hypoxia-inducible factor-1a (HIF-1a) by heterotopic versus normotopic endometrium in women with adenomyosis and found that both were increased, particularly in epithelial cells. Furthermore, Kang et al (2009) investigated four VEGF polymorphic alleles and found significant differences between adenomyosis patients and a control group in the allele frequencies and genotype distributions.…”
Section: Altered Endometrial Function and Receptivitysupporting
confidence: 79%
“…Similar results for MMP2 were obtained by Tokyol et al (2009). Subsequently, Goteri et al (2009) compared in the same women the expression of VEGF and hypoxia-inducible factor-1a (HIF-1a) by heterotopic versus normotopic endometrium in women with adenomyosis and found that both were increased, particularly in epithelial cells. Furthermore, Kang et al (2009) investigated four VEGF polymorphic alleles and found significant differences between adenomyosis patients and a control group in the allele frequencies and genotype distributions.…”
Section: Altered Endometrial Function and Receptivitysupporting
confidence: 79%
“…Hypoxia-inducible factor-1 (HIF-1) is a master transcription factor that mediates the hypoxic effect and plays a key role in VEGF-induced angiogenesis [20,21]. Recent data indicate a possible role for HIF-1 in the pathogenesis and development of endometriosis and adenomyosis [21][22][23]. NO is a lipid-soluble gaseous free radical produced during the enzymatic conversion of L-arginine to L-citrulline by NO synthase (NOS) enzyme and involved in both inflammation and neoangiogenesis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of vessels supplying a large uterus becomes thicker (22). Goteri et al (4) claimed that there has been a marked increase in the development of microvessels in patients with ADS. The lesions of ADS have been shown to be hypervascularized tissues due to high VEGF content (23).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ADS in hysterectomy specimens was found to be 28.2% in a study (2). Studies have demonstrated the occurrence of invasive adenomyotic lesions associated with increased levels of matrix metalloproteinases (MMPs) and showed increased levels of vascular endothelial growth factor (VEGF) in patients with ADS (3,4). The progressive enlargement of the uterus due to adenomyotic lesions is considered to cause symptoms such as abnormal uterine bleeding (AUB), dysmenorrhea, and uterine tenderness (5).…”
Section: Introductionmentioning
confidence: 99%